Unnecessary Frills: Communality as a Nice (But Expendable) Trait in Leaders - Vial, Andrea C.; Napier, Jaime L. (Frontiers in Psychology, 2018)
Although leader role expectations appear to have become relatively more compatible with stereotypically feminine attributes like empathy, women continue to be highly underrepresented in leadership roles. We posit that one reason for this disparity is that, whereas stereotypically feminine traits are appreciated as nice “add-ons” for leaders, it is stereotypically masculine attributes that are valued as the defining qualities of the leader role, especially by men (who are often the gatekeepers to these roles). We assessed men’s and women’s idea of a great leader with a focus on gendered attributes in two studies using different methodologies. In Study 1, we employed a novel paradigm in which participants were asked to design their “ideal leader” to examine the potential trade-off between leadership characteristics that were more stereotypically masculine (i.e., agency) and feminine (i.e., communality). Results showed that communality was valued in leaders only after meeting the more stereotypically masculine requirements of the role (i.e., competence and assertiveness), and that men in particular preferred leaders who were more competent (vs. communal), whereas women desired leaders who kept negative stereotypically masculine traits in check (e.g., arrogance). In Study 2, we conducted an experiment to examine men’s and women’s beliefs about the traits that would be important to help them personally succeed in a randomly assigned leader (vs. assistant) role, allowing us to draw a causal link between roles and trait importance. We found that both men and women viewed agentic traits as more important than communal traits to be a successful leader. Together, both studies make a valuable contribution to the social psychological literature on gender stereotyping and bias against female leaders and may illuminate the continued scarcity of women at the very top of organizations, broadly construed.